Pemanfaatan Lingkungan Alam sebagai Sumber Belajar dalam Pembelajaran IPA SMP - Sakinah, Amanda; Utami, Tika Wahyu; Rahayu, Zuninda; Ismawati, Riva (Universitas PGRI Semarang, 2024)
Science learning is often considered difficult by students because students think that science material is abstract in nature. Science learning is learning related to real life that requires direct experience from the natural environment so that learning is more meaningful. The natural environment is the environment around us that can be used as a learning resource. The purpose of learning science is to provide knowledge (cognitive), skills (psychomotor), and attitudes (affective). The natural environment that can be used as a source of learning science is rice fields. This study aims to analyze the use of the natural environment as a learning resource in junior high school science learning. This study uses the literature study method with the results of the data in the form of written words. Based on the analysis of the articles that we have done, we obtained data that the use of the natural environment as a learning resource in junior high school science learning has a significant influence on science process skills. The success of improving science process skills is due to the impact of using learning facilities using nature. The purpose of writing this article is to describe the use of the natural environment as a learning resource in junior high school science learning.